Rules-Based Monetary Policy and the Threat of Indeterminacy When Trend Inflation is Low - Hashmat Khan; Louis Phaneuf; Jean Gardy Victor (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
Indeterminacy in new Keynesian models with Calvo-contracts can occur even at low trend inflation levels of 2 or 3%. The interaction of trend inflation with nominal wage rigidity and trend growth in output causes large distortions in the steady state and expands the indeterminacy region. Consequently, even interest rate rules with strong inflation responses may not be sufficient to ensure determinacy. A policy rule reacting to output growth but not to output gap significantly increases the prospect of determinacy. Although the threat of indeterminacy is less severe under Taylorcontracts, significant departures from the original Taylor principle are required for determinacy.
Keywords: 330